Do Temporary Increases in Information Asymmetry Affect the Cost of Equity? - Levi, Shai; Zhang, Xiao-Jun (Management Science, 2015)
Prior literature finds that long-lasting changes in firms' disclosure policies and information environment affect the cost of equity. Information asymmetry, however, also changes during the fiscal quarter. Firms disclose information periodically, and in between disclosure dates, traders can obtain private information, and adverse-selection risk increases. Such temporary increases in information asymmetry are usually considered to be diversifiable or too small to impact expected stock returns. In addition, investors may postpone trades or sell other assets in their portfolio on high information asymmetry days. We, however, find that returns increase significantly on days during the fiscal quarter when adverse-selection risk is high and liquidity low. Consistent with theory, we show that temporary asymmetry affects returns when investors demand liquidity and market makers bear risk for carrying capacity and providing it. This paper was accepted by Mary Barth, accounting.